2020
DOI: 10.12968/ajmw.2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Perception of risk and prevention of gestational diabetes mellitus among pregnant women in Ibadan, Nigeria

Abstract: Background/Aims An increasing prevalence rate of gestational diabetes mellitus has been recorded in developing countries including Nigeria, yet it is largely a preventable condition. There is a lack of literature on the perception of risk and prevention of gestational diabetes among pregnant women in Ibadan, Nigeria. The aim of this study was to determine perception of risk and knowledge of preventative measures among pregnant women in Ibadan, Nigeria. This will inform health professionals on possible improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…A statistically significant association between knowledge about GDM among pregnant women attending antenatal clinics in University College Hospital, Ibadan and their perceived risk of developing GDM. This is consistent with that of Akinwaare et al 22 in a primary healthcare centre which also reported poor knowledge of GDM among more than half of the participants and a good perception of the risk of developing diabetes in pregnancy amongst the minority. There is a statistically significant association between the attitude of pregnant women attending antenatal clinics in UCH towards GDM and their perception of GDM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A statistically significant association between knowledge about GDM among pregnant women attending antenatal clinics in University College Hospital, Ibadan and their perceived risk of developing GDM. This is consistent with that of Akinwaare et al 22 in a primary healthcare centre which also reported poor knowledge of GDM among more than half of the participants and a good perception of the risk of developing diabetes in pregnancy amongst the minority. There is a statistically significant association between the attitude of pregnant women attending antenatal clinics in UCH towards GDM and their perception of GDM.…”
Section: Discussionsupporting
confidence: 91%
“…21 Akinwaare et al in a study to determine the perception of risk and knowledge of preventive measures among pregnant women found out that even though the majority of the pregnant women had poor knowledge of GDM as well as it preventive measures, most of the women perceived themselves to be at low risk. 22 Knowledge of any condition is only complete if the individual can comprehend all the associated factors of the particular condition. Meanwhile, poor awareness about GDM results in poor preventive and management strategies.…”
Section: Introductionmentioning
confidence: 99%
“… Rhoads-Baeza and Reis (2010) in Spain also reported that a few of the participants believed that fate had a role to play in developing the illness, thus anyone who is predestined to develop the illness will, no matter the preventive measures put in place. Although the risk of GDM can be modified by preventive lifestyle practices, Akinwaare et al (2020) in the context of Nigeria discovered that majority of the participants believed that their risk of developing GDM was low thus efforts to prevent the condition were minimal. Similar findings were reported in a study carried out in the southwestern part of Nigeria where about 31% of the participants strongly believed that diseases are a result of spiritual influences ( Adegoke, 2008 ).…”
Section: Exercise As a Preventive Measurementioning
confidence: 99%
“…1 GDM arises due in part to the aberrations in insulin receptors and signalling and this can resolve after delivery, however, it is established that between 40-60% of GDM patients develop type 2 diabetes mellitus (T2DM) in ten to twenty years. 2,3 The various risk factors (RFs) for GDM include older age, overweight and obesity, previous GDM, excessive weight gain during pregnancy, a family history of diabetes, polycystic ovary syndrome, habitual smoking and a history of stillbirth or giving birth to an infant with a congenital abnormality. 4 Studies have reported a wide range of prevalence values.…”
Section: Introductionmentioning
confidence: 99%